Design and implementation of an archetype based interoperable knowledge eco-system for data buoys - Stacey, Paul; Berry, Damon (OCEANS 2017 - Aberdeen, 2017)
This paper describes the ongoing work of the authors in translating two-level system design techniques used in Health Informatics to the Earth Systems Science domain. Health informaticians have developed a sophisticated two-level systems design approach for electronic health documentation over many years, and with the use of archetypes, have shown how knowledge interoperability among heterogenous systems can be achieved. Translating two-level modelling techniques to a new domain is a complex task. A proof-of-concept archetype enabled data buoy eco-system is presented. The concept of operational templates-as-aservice is proposed. Design recommendations and implementation experiences of re-working the proposed architecture to run on ultra-resource constrained data buoy platforms using templates-as-service are described.